Anatomical Variations of the Nasal Conchae and Nasal Septum and their Relationships with Alterations in the Maxillary Sinus Mucosa: A Study on Cone-beam Computed Tomography Images - Luara da Silveira Roberto Almeida; Aline da Silva Ruffo; Karina Lopes Devito (International Archives of Otorhinolaryngology)
Introduction In the literature, there is divergence about the relationship between anatomical variations of the turbinates and nasal septum (NS) and alterations in the maxillary sinus (MS) mucosa.